Group B streptococcal disease in UK and Irish infants younger than 90 days, 2014–15: a prospective surveillance study. Issue 1 (January 2019) - O'Sullivan, Catherine P; Lamagni, Theresa; Patel, Darshana; Efstratiou, Androulla; Cunney, Robert; Meehan, Mary; Ladhani, Shamez; Reynolds, Arlene J; Campbell, Ruth; Doherty, Lorraine; Boyle, Margaret; Kapatai, Georgia; et al.
Summary: Background: Group B streptococcus is a leading cause of serious infection in young infants in many countries worldwide. We aimed to define the burden and clinical features of invasive group B streptococcal disease in infants younger than 90 days in the UK and Ireland, together with the characteristics of disease-causing isolates. Methods: Prospective, active national surveillance of invasive group B streptococcal disease in infants younger than 90 days was done from April 1, 2014, to April 30, 2015, through the British Paediatric Surveillance Unit, microbiology reference laboratories, and national public health agencies in the UK and Ireland. Early onset was defined as disease in the first 6 days of life and late onset was defined as 7–89 days of life. Incidence was calculated using livebirths in 2014 (after adjustment for the 13-month surveillance period). Isolates were characterised by serotyping, multilocus sequence typing, and antimicrobial susceptibility testing. Findings: 856 cases of group B streptococcus were identified in 2014–15, an incidence of 0·94 per 1000 livebirths (95% CI 0·88–1·00). Incidence for early-onset disease (n=517) was 0·57 per 1000 livebirths (95% CI 0·52–0·62), and for late-onset disease (n=339) was 0·37 per 1000 livebirths (0·33–0·41). 53 infants died (case fatality rate 6·2%), of whom 27 had early-onset disease (case fatality rate 5·2%) and 26 had late-onset disease (case fatality rate 7·7%). The predominant serotypes were III (241 [60%] of 402 serotyped isolates) and Ia (69 [17%]); five serotypes (Ia, Ib, II, III, V) accounted for 377 (94%) of all serotyped isolates. Interpretation: The incidence of invasive infant group B streptococcal disease in the UK and Ireland has increased since a comparable study done in 2000–01. The burden of early-onset disease has not declined despite the introduction of national prevention guidelines. New strategies for prevention are required. Funding: Meningitis Now.